Parent-report instruments for assessing feeding difﬁculties in children with neurological impairments: a systematic review - Jaafar, Nurul Hazirah; Othman, Azizah; A Majid, Noorizan; Harith, Sakinah; ZAMH, Zabidi-Hussin (Mac Keith Press, 2018)
AIM This study aimed to review the psychometric properties and clinical application of parent-report instruments that assess feeding difﬁculties in children with neurological impairments. METHOD Papers were identiﬁed through ﬁve electronic databases based on 15 keywords and were included if they met the following criteria: published in English, described the implementation of parent-report instruments, and included children with neurological impairments (either in the report or a related study population). RESULTS In total, 1220 relevant abstracts were screened and 22 full-text articles were evaluated. The following six parent-report instruments met the inclusion criteria: (1) Screening Tool of Feeding Problems applied to children, (2) Paediatric Eating Assessment Tool, (3) Paediatric Assessment Scale for Severe Feeding Problems, (4) Montreal Children’s Hospital Feeding Scale, (5) Children’s Eating Behaviour Inventory, and (6) Behavioural Paediatric Feeding Assessment Scale (BPFAS). Based on comprehensive psychometric testing and consistently good results, the BPFAS was considered the most valid and reliable instrument. The BPFAS also showed good clinical applicability because it was readily available, required a short administration time, and used a simple scoring system. INTERPRETATION We reviewed the available parent-report instruments for assessing feeding difﬁculties in children with neurological impairments. The BPFAS had the best psychometric properties and clinical applicability.